Capturing gendered aspects of active aging in China: Insights drawn from the Active Aging Index in comparison with EU countries. Issue 1 (20th December 2020) - Um, Jinpil; Zaidi, Asghar; Parry, Jane; Xiong, Qian
Abstract: This paper extends the Active Aging Index (AAI) to China to measure active aging among men and women over the age of 55. The strength of the AAI approach lies in its selection of a dashboard of multidimensional indicators of active aging, which are then aggregated into composite measures. The analysis used here considers the differences between men and women on 22 AAI indicators and their aggregations. China scores high on the first domain of the AAI (employment), is comparable with the EU countries on the second (participation in society), and scores lower on the third and fourth domains (independent and health living, and capacity and enabling environment). China has one of the largest gender gaps in active aging, especially in employment, but also in the domain of "Independent Living." The comparison with EU countries points to a number of policy priorities and learnings, including the removal of disincentives to women working longer, namely differential mandatory and occupational retirement ages, and the introduction of measures to make workplaces more age and gender friendly.